Ear tissue as a diagnostic sample for pestivirus detection in semi-domesticated Eurasian tundra reindeer (Rangifer tarandus tarandus) in Norway - Malmström, Ester; Tryland, Morten; Passler, Thomas; Becker, Alice; Bull-Aurbakken, Stine; Silvis, Scott; Phillips, Rachel; Falkenberg, Shollie (Frontiers in Microbiology, 2025)
IntroductionAlthough eradication programs have successfully controlled pestivirus infections in domestic livestock across Fennoscandia, serological evidence suggests that several free-ranging, semi-domesticated reindeer herds are exposed to and possibly endemically infected with pestivirus(es). While the significant economic impact of pestiviruses on domestic animals is well documented, their effects on reindeer remain poorly understood. Attempts to isolate and characterize these pestiviruses from seropositive reindeer herds have so far been unsuccessful, despite analyses of serum and nasal swab samples by multiple studies. Ear tissue is commonly used to detect cattle persistently infected (PI) with pestivirus and utilized for both screening and controlling infection. Despite its practicality in cattle, ear tissue has not been utilized for the demonstration of pestivirus in reindeer. The current study aimed to examine ear tissue as sample material for the detection and isolation of pestivirus in Norwegian semi-domesticated reindeer herds.MethodsEar tissue from 3,453 reindeer calves from three geographically distinct locations were assessed by conventional reverse transcriptase polymerase chain reaction (RT-PCR), antigen capture ELISA (ACE), and virus isolation.ResultsA total of 24 (0.7%) individual ear tissue samples were considered potentially positive by RT-PCR but were negative by ACE, and no virus could be isolated from any of the samples. Three commercially available reverse transcription quantitative polymerase chain reaction (RT-qPCR) assays for the diagnosis of bovine viral diarrhea virus (BVDV) were also employed from which a CT-value of less than 40 was detected in only one sample (CT 36.95).DiscussionWhile potential positive ear tissue samples were observed in this study, it is unknown if low viral load, pestivirus genetic diversity, or sample suitability contributed to the inability to confirm pestivirus-specific RNA nor viable virus particles in the samples. The impact of pestivirus infections on health and welfare of reindeer and effect on eradication programs in Fennoscandian livestock remain undetermined and the results from this study emphasize the critical need for multidisciplinary research regarding this topic.